Reusing Implicit Cooperation. A Novel Approach to Knowledge Management - Luigi Lancieri (tripleC: Communication, Capitalism & Critique)
The study described in this paper deals with information reuse obtained by implicit co-operation, particularly by recycling the contents of a proxy cache (shared memory). The objective is to automatically feed a Web server with large multimedia objects implicitly centred on community fields of interests. We show that the strategy of reusing previously downloaded information provides interesting advantages at a low cost; in particular, to reduce Web access time, to improve information retrieval, and to reduce Internet bandwidth use. Moreover, we use the conceptual frameworks of forgetting and collective intelligence to develop a model on which the operation of implicit cooperation is based.